Porous alumina ceramics by gel casting: Effect of type of sacrificial template on the properties. Issue 2 (27th June 2019) - Hooshmand, Saleh; Nordin, Jan; Akhtar, Farid
Abstract: The effect of type of sacrificial template on the processing and properties of porous alumina ceramics was investigated. Two templates, (a) hollow pre‐expanded polymer spheres (Expancel) and (b) dense glassy carbon, were used to prepare porous alumina ceramics by gel casting. The results showed that the burnout of sacrificial expandable polymer microspheres from alumina ceramics was 10 times faster than glassy carbon without compromising the compressive strength. Moreover, the effect of the size of the porous ceramic component during the burnout showed that the template decomposition and the escape of the formed gases took a longer time for the thicker specimens than the thinner one and it was significant in case of glassy carbon. It was found that the burnout of expandable microspheres could happen at a faster rate, and the time of the burnout cycle could be reduced significantly to save energy while keeping the mechanical strength twice as high than porous alumina ceramics after burnout of glassy carbon. Furthermore, the CO2 emissions during the burnout of sacrificial templates and the microstructure of the prepared porous alumina were compared for these two types of sacrificial templates. The prepared foams with pre‐expanded microspheres showed potential for being used in industrial applications, where the decreasing of the released gases is critical for saving time and energy for the fabrication of large ceramic parts. Abstract : Two templates, (a) hollow pre‐expanded polymer spheres (Expancel) and (b) dense glassy carbon, were used to prepare porous alumina ceramics by gel casting. The mechanical properties showed that the compressive strength of the foams prepared by using the glassy carbon was lower than the ones using Expancel.